Features of inpatient treatment of patients with skin diseases and sexually transmitted infections - Korolenko, V. V.; Gruzieva, T. S. (Pathologia, 2020)
Aim of the study is to analyze the use of inpatient beds for treatment of patients with dermatoses and sexually transmitted infections (STIs). Materials and methods. The indicators of treatment and preventive care for patients with dermatoses and STIs in Ukraine for 2009–2019 were analyzed using statistical, bibliosemantic methods, systematic approach and analysis. Results. In general, in Ukraine there is a tendency to reduce the availability of dermatovenereological beds and the average length of stay of a patient in such beds. During 2009–2015, the average number of working days of such beds decreased, after which it increased. The correlation between the indicators of availability and performance of such beds, taking into account the incidence of STIs and late syphilis, were determined. At the same time, the observed decrease in the incidence of STIs and the increase in late syphilis may indicate insufficient detection of these nosologies in the early stages. Dermatovenereological beds are significantly overloaded. Conclusions. A significant reduction of the resources of the dermatovenereological service, including institutions, provision and operation of inpatient beds has led to an intensification of their use and a reduction in the availability of medical care. The tendency to increase of late, complicated forms of venereal diseases, formation of the corresponding negative consequences for health of the population cause need for improvement of dermatovenereological service. It is advisable to ensure proper training of primary care physicians, in particular family physicians, in the management of patients with common uncomplicated dermatoses and STIs after consultation with dermatovenereologists, optimization of coordination of various levels of medical care, as well as the use of telemedicine screening and monitoring.